Application of pH and TDS Sensors in NFT Hydroponic Systems to Increase the Growth Quantity of Pakcoy (Brassica rapa L.) - Pertiwi, Lastri; Fevria, Resti; Vauzia, Vauzia; Anhar, Azwir (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Pakcoy is a type of vegetable widely used as a staple food or as a complementary dish; however, its production in Indonesia tends to be unstable. This study aimed to improve the growth of pakcoy using an NFT hydroponic system equipped with IoT-based pH and TDS sensors. The research was conducted at Alfi Hydroponik Padang and the Biology Department Laboratory, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, from June to September 2025, using a completely randomized design with 2 treatments, each consisting of 9 replications. The data were analyzed using an independent t-test in SPSS at a 5% significance level. The results showed that the use of sensors was significantly more effective than manual methods, with average plant height of 25.889 cm, 19.44 leaves, leaf area of 503.117 cm², fresh weight of 89.224 g, and dry weight of 48.474 g. These results indicate that the application of IoT-based pH and TDS sensors can enhance the growth of pakcoy in a hydroponic system.